A THERAPEUTIC APPROACH OF SUDHA VARGA DRAVYA W.S.R. TO GASTROINTESTINAL DISORDER (AYUSHDHARA, 2016)
The human Gastro intestinal tract is responsible for transporting and digesting food stuffs, absorbing nutrients and expelling waste. Any interruption or change in physiology of GIT results in various disease like Hyperacidity, Peptic ulcer, duodenal ulcer, Irritable Bowel Syndrome, Gastro-Esophageal Reflux Disorder etc. In Ayurveda all these diseases comes under Annavaha Srotas Vikara. There are many treatment modalities available in Ayurveda but Sudha vargiya Dravyas describe in Rasa-shastra literature plays an important role in the treatment of GIT disorders. Bhasmas of Sudha vargiya Dravyas have attained importance in prevention and cure of conditions such as AmlaPitta (hyperacidity), Grahani (Irritable Bowel Syndrome), Annadrava shula (Gastric ulcer), Parinaam shula (Duodenal ulcer), Atisara (Diarrhoea) etc. Bhasmas are considered as nano medicine in Ayurveda which is therapeutically very potent in small dose, quick acting and without specific taste. All the drugs in Sudha Varga have calcium in compound form, as salt. Calcium has very essential role in physiology related to bone structure as well as regulation of Gastro intestinal secretions. As these having Sheet virya in all the Sudha vargiya Dravyas the acid neutralizing capacity is present due to higher pH value.